Imagining a meshwork of urban nature: Lawrence Halprin and Panhandle Parkway in the San Francisco - Su, Meng-Tsun (International Planning History Society Proceedings, 2018)
The unbuilt project of Panhandle Freeway in San Francisco from the early 1960s is a unique case in the politics of design during the heyday of urban renewal in the United States in the early 1960s. The close collaboration between highway engineers and landscape architect Lawrence Halprin on this project also exemplifies cross-disciplinary thinking in redefining natural processes in the city. While Halprin emphasized the visual and visceral experience of moving through the highways integrated with parks and residential apartments, the civic function of urban freeway clashed with the local communities that would be displaced by the construction. The aesthetics of mobility eulogized a regional vision shared by Halprin and his friends informed their active involvement with the infrastructural design of the Bay Area. It presents an alternative to the criticism of the urban renewal of the 1960s. Nevertheless, the residents worked with the city council on the successful revolt against Panhandle Freeway, and none of the alternative routes was constructed, leaving the gap between southern San Francisco and Golden Gate Bridge to local traffic. While some critics see Halprin’s freeway design as an ameliorative disguise, his schemes open up a dialogue between social and aesthetic aspects of the mobility. In doing so, his interweaving of urban ecology and infrastructure marked the evolution of scenic parkways to urban freeway in landscape architectural practices. The lesson of Panhandle Freeway is not only a matter of coexistence, it also foreshadowed the open-ended methodology in planning and design.